Effects of milk product intake on thigh muscle strength and NFKB gene methylation during home-based interval walking training in older women: A randomized, controlled pilot study - Masuki, Shizue; Nishida, Kensei; Hashimoto, Shigenari; Morikawa, Mayuko; Takasugi, Satoshi; Nagata, Masashi; Taniguchi, Shun'ichiro; Rokutan, Kazuhito; Nose, Hiroshi (PLOS ONE, 2017)
Background Muscle atrophy with aging is closely associated with chronic systemic inflammation and lifestyle-related diseases. In the present study, we assessed whether post-exercise milk product intake during 5-month interval walking training (IWT) enhanced the increase in thigh muscle strength and ameliorated susceptibility to inflammation in older women. Methods Subjects [n = 37, 66±5 (standard deviation) yrs] who had been performing IWT for >6 months participated in this study. They were randomly divided into the following 3 groups: IWT alone (CNT, n = 12), IWT + low-dose post-exercise milk product intake (LD, n = 12; 4 g protein and 3 g carbohydrate) or IWT + a 3-times higher dose of milk product intake than the LD group (HD, n = 13). They were instructed to repeat ≥5 sets of fast and slow walking for 3 min each at ≥70% and 40% peak aerobic capacity for walking, respectively, per day for ≥4 days/week. Results After IWT, thigh muscle strength increased in the HD group (8±2%) more than in the CNT group (-2±3%, P = 0.022), despite similar IWT achievements between the groups (P>0.15). Pyrosequencing analysis using whole blood showed that methylation of NFKB1 and NFKB2, master genes of inflammation, was enhanced in the HD group (29±7% and 44±11%, respectively) more than in the CNT group (-20±6% and -10±6%, respectively; P<0.001). Moreover, the genome-wide DNA methylation analysis showed that several inflammation-related genes were hyper-methylated in the HD group compared with that in the CNT group, suggesting greater pro-inflammatory cytokine gene suppression in the HD group. Conclusion HD milk product intake after exercise produced a greater percent increase in thigh muscle strength and NFKB1 and NFKB2 gene methylation during IWT in physically active older women. Trial registration UMIN-CTR No. UMIN000024544 and No. UMIN000024912